Prehospital Resuscitation Performed on Hypotensive Trauma Patients in Afghanistan: The Prehospital Trauma Registry Experience - Schauer, Steven G; Naylor, Jason F; April, Michael D; Fisher, Andrew D; Cunningham, Cord W; Fernandez, Jessie Renee D; Shreve, Brian P; Bebarta, Vikhyat S (Military medicine, 2019)
Abstract Introduction Hemorrhage is the leading cause of potentially preventable death on the battlefield. Hypotension in the setting of trauma portends a higher rate of mortality. We describe the interventions for trauma-related hypotension performed in the prehospital combat setting in accordance with Tactical Combat Casualty Care (TCCC) guidelines. Materials and Methods We searched the Prehospital Trauma Registry for casualties from January 2013 to September 2014. Within that group, we searched for all casualties with documented hypotension by either measured systolic blood pressure ≤90 mmHg or a weak or absent radial pulse documented by the prehospital provider. We used descriptive statistics to analyze the interventions performed in our study sample. Results Of the 705 casualties available for query, 134 (19.0%) casualties with documented hypotension met inclusion criteria. Most casualties with hypotension had an alert mental status (70.1%), had a medical officer in their chain of care (59.0%), were Afghan (64.2%), and evacuated on an urgent status (78.4%). Explosives were the most frequent mechanism of injury (50.7%). There were 42 fluid administrations documented on 33 (24.6%) casualties. The most common fluid administered was normal saline (52.4%) followed by hetastarch solution (33.3%). There was one documented use of a fluid warmer in this cohort. One subject received four units of packed red blood cells. No other casualties had documented blood product administration. There were no documented administrations of PlasmaLyte. There were four casualties that received lactated Ringer’s. Conclusion Most casualties with documented hypotension after trauma in the Prehospital Trauma Registry did not receive prehospital blood or fluid intervention. Of the interventions performed, most did not match with contemporary TCCC guidelines.